Effect of Side Chain Length on Segregation of Squalane between Smectic Layers Formed by Rod-Like Polysilanes - Tanaka, Takuya; Kato, Itsuki; Okoshi, Kento (Journal of Research Updates in Polymer Science, 2018)
The segregation of spherical molecules (squalane) between the smectic layers of rod-like polymers (polysilanes) with narrow molecular weight distributions were investigated by synchrotron radiation small-angle X-ray scattering (SR-SAXS), atomic force microscopy (AFM) observations, and molecular dynamics simulations to elucidate the effect of the polymer side chain length on the segregation. It has been theoretically predicted that the smectic phase of the rod-like particles will be stabilized by inserting the spherical particles into the interstitial region between the smectic layers when the diameter of the spherical particles is smaller than that of the rod-like particles whose length is sufficiently long. We found that the segregation of squalane was unaffected by the molecular weight (Mw) of the polysilane in the range of 9,200-44,100 g/mol, and the diameter of the polysilane showed the optimal size of 5.64 nm for the segregation of squalane whose diameter is 6.57 nm although the origin of these inconsistencies between theory and experiment is currently not clear.